2020
DOI: 10.1155/2020/9814916
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time PCR and Quantitative Culture for Mycoplasma pneumoniae Load in Pharyngeal Swabs from Children at Preliminary Diagnosis and Discharge

Abstract: Background. Extensive studies have focused on the diagnosis and treatment of Mycoplasma pneumoniae infection; however, rare studies investigated the posttreatment conditions. We analyzed the carrying status of M. pneumoniae in the respiratory tract of children before and after treatment. Methods. Ninety-two children with M. pneumoniae pneumonia were included in this study. Clinical data were obtained from each patient, and pharyngeal swab sampling was performed at preliminary diagnosis and discharge. Real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…Real-time PCR, a well-developed practical method for the detection of infective pathogens, has been widely used for the clinical diagnosis of M. pneumoniae ( Dumke et al, 2007 ; Winchell and Mitchell, 2013 ; Zhao et al, 2020 ). However, it relies on a standard curve to calculate the DNA copy number, which differs among experiments and thus complicates the diagnostic process.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR, a well-developed practical method for the detection of infective pathogens, has been widely used for the clinical diagnosis of M. pneumoniae ( Dumke et al, 2007 ; Winchell and Mitchell, 2013 ; Zhao et al, 2020 ). However, it relies on a standard curve to calculate the DNA copy number, which differs among experiments and thus complicates the diagnostic process.…”
Section: Discussionmentioning
confidence: 99%
“…Debido a las ventajas de tiempos de respuesta cortos, alta sensibilidad y especificidad, y no afectarse por la respuesta inmunológica, la PCR se ha convertido en opción preferida para el diagnóstico temprano de M. pneumoniae en el medio asistencial [ 28 , 29 ]. Sin embargo, tiene algunas limitaciones, la necesidad de muestras de alta calidad, y la posibilidad de que los inhibidores de la PCR conduzcan a resultado falsos negativos [ 30 ].…”
Section: Diagnósticounclassified
“…Los antibióticos más utilizados para el tratamiento en las neumonías por este microorganismo, sobre todo en niños, son los macrólidos que tienen acción antiinflamatoria además de antibiótica, lo que contribuye a la mejoría del paciente [ 30 ]. Dentro de los macrólidos, la azitromicina, roxitromicina o claritromicina se prefieren a la eritromicina por su mejor tolerancia, su mejor administración y menor duración de tratamiento.…”
Section: Tratamientounclassified
“…Clinically, erythromycin, as the first choice of macrolides, can maintain a high concentration in serum, so as to completely control mycoplasma pneumonia [16] , some studies have found that macrolide antibiotics have significant effect on improving the clinical efficacy of patients with MPP. Moreover, some studies have reported that macrolide resistant children have less inhibitory effect on microorganisms and may not achieve the effect of treating MPP [17] . Since Japan first reported macrolide resistance 1970, the global prevalence of macrolide resistant MP has increased to 10 %-30 %, which will eventually lead to severe refractory MP [18] .…”
Section: Total Clinical Effective Rate=(significantly Effective+effec...mentioning
confidence: 99%